Archetypal Approach to Eliot's “The Waste Land” - Rinku Nandi (PostScriptum: An Interdisciplinary Journal of Literary Studies, 2016)
In literary criticism archetype denotes a primordial image. It is through primordial images that universal archetypes are experienced and the unconscious is revealed. In “The Waste Land” the central theme of sterility is expressed through the central myth of ‘death-rebirth archetype’ very minutely. Eliot uses the mythic mode with the archetypal approach in “The Waste Land”. This paper tries to capture this mythic sensibility, in its limited way, as expressed in “The Waste Land”.